PEMASARAN GULA KELAPA DI KABUPATEN INDRAGIRI HILIR MELALUI PENDEKATAN STRUKTUR, PERILAKU & PENAMPILAN PASAR - Evy Maharani; Susy Edwina; Yeni Kusumawaty (Fakultas Pertanian, Universitas Riau, 2011)
This research is aimed to analyze the marketing of coconut sugar based on the structure,conduct and performance of the market. This research is carried out in Indragiri HilirRegency by using survey method over the number of 32 samples. The samples are takenbay snowball sampling start with the sugar makers. The results of this research show thatmarket structure is likely to be monopsony, where trader middle man traders are moredominant while sugar makers are price taker. There are three marketing channels in thisresearch area. From market performance criteria it shows that the first channel is moreprofitable since the costs are much lower and more efficient compare to channel 2 and 3.Keywords: structure, coconut sugar, performance, margin.